2013
DOI: 10.1128/jb.01034-13
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Alternative Sigma Factor SigX Regulon and Its Implications for Pseudomonas aeruginosa Pathogenicity

Abstract: e Pseudomonas aeruginosa is distinguished by its broad metabolic diversity and its remarkable capability for adaptation, which relies on a large collection of transcriptional regulators and alternative sigma () factors. The largest group of alternative factors is that of the extracytoplasmic function (ECF) factors, which control key transduction pathways for maintenance of envelope homeostasis in response to external stress and cell growth. In addition, there are specific roles of alternative factors in regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
67
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(78 citation statements)
references
References 57 publications
8
67
0
3
Order By: Relevance
“…In these conditions, the pel gene cluster was not identified as a putative SigX target (Gicquel et al ., ). In a study integrating chip‐on‐chip experiments and transcriptomic assays based on P. aeruginosa PA14 and its isogenic sigX mutant, pel was not identified as a direct SigX target (Blanka et al ., ). Furthermore, we were unable to find a putative SigX consensus binding motif (Blanka et al ., ) in the promoter region of pelA (data not shown).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In these conditions, the pel gene cluster was not identified as a putative SigX target (Gicquel et al ., ). In a study integrating chip‐on‐chip experiments and transcriptomic assays based on P. aeruginosa PA14 and its isogenic sigX mutant, pel was not identified as a direct SigX target (Blanka et al ., ). Furthermore, we were unable to find a putative SigX consensus binding motif (Blanka et al ., ) in the promoter region of pelA (data not shown).…”
Section: Resultsmentioning
confidence: 97%
“…SigX is an ECF sigma factor that is involved in fatty acid synthesis (Boechat et al ., ; Blanka et al ., ) and in biofilm formation (Gicquel et al ., ; Blanka et al ., ). As we have previously shown that SigX activity was increased in high sucrose‐containing medium (Bouffartigues et al ., ), we suspected SigX to be involved in the molecular mechanism linking sucrose and biofilm formation.…”
Section: Resultsmentioning
confidence: 99%
“…6). A study showed that osmotic stress changes the fatty acid profile of P. aeruginosa through an alternative sigma factor (SigX)-dependent influence on accAB transcription (36). However, high salt concentrations might also stimulate the Wsp cascade through an alteration of the mechanical properties of the cell membrane because of the introduction of unsaturated fatty acids (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cell cultures were grown and maintained at 37°C in the presence of 5% CO 2 . Host cell viability was monitored during live bacterial infections and flagellin incubation assays and were performed directly on collected A549-Gluc cell supernatants as previously described (34,35). Percent viability was calculated as the relative light unit (RLU) ratio between infected and uninfected controls.…”
Section: Methodsmentioning
confidence: 99%